Textbooks for primary school in the reception of Western Ukrainian teachers (the second half of the XIX – early XX centuries) - Vykhrushch Nataliya (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2021)
The process of creating school textbooks is continuous and is based on positive retrospective experience and modern demands of society to the content of education. Under such conditions, the study of the attitude of practising teachers and scholars towards textbooks for primary school in the second half of the nineteenth – early twentieth centuries is relevant for pedagogical science. The article analyses the ideas of Western Ukrainian teachers of the second half of the XIX - early XX centuries on the problem of compiling and using school textbooks, their role in education. The analysis of positive and negative characteristics of textbooks for primary school of the period under study is carried out. The main socio-economic and political factors influencing the state and functioning of textbooks for primary school are considered. The aim of the article is to analyse publications and ideas of Western Ukrainian teachers and scholars towards the structure of textbooks for primary school, scientific and accessible content, brevity, accuracy and quality of presentation, the language of textbooks, clarity of definitions, unambiguous use of terms. The research methodology involved: bibliographic search, comparative analysis, systematization and theoretical generalization, content analysis for analytical processing of literature. During the period under study, theoretical substantiation of textbooks for primary school structure, content, didactic principles of text construction began. The importance of visual instruction in primary school was emphasised. Numerous examples have shown the fact that teachers' dissatisfaction with school textbooks was due to excessive volume, numerous unsuccessful passages of texts with dry content, complex, unsuitable for the children’s style, terms and long sentences. Their main flaw was that the material was presented in a dry and tendentious way, thus creating obstacles to the development of interest in independent reading outside the school.